1999
DOI: 10.1021/la9902441
|View full text |Cite
|
Sign up to set email alerts
|

Surface Effects on Cation Transport across Porous Alumina Membranes

Abstract: Transport behavior of monovalent and divalent solutes across mesoporous Anopore γ-alumina membranes was investigated as a function of pore diameter, pH, ionic strength, and nature of the salt or complexing species in solution. Radiotracers 137 Cs, 85 Sr, 22 Na, and 45 Ca were present in the feed solutions at very low concentrations, ranging from 10 -9 to 10 -12 M and total salt concentrations from 0.1 to 10 -4 M. The divalent cations Ca 2+ and Sr 2+ exhibit lower diffusion rates (3-7 times slower) than the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
69
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 9 publications
8
69
0
Order By: Relevance
“…However, when we used o-phosphoric acid as the acid dopant in DHB as the matrix, the MS signal of tetraphosphopeptide (m/z 3122) and another phosphopeptide (m/z 2556) were observed°after°the°enrichment°process°with°PAA° (Figure°5).°In°addition°to°the°enhanced°ionization°of°phos-phopeptide, phosphoric acid might decrease the interactions between the PAA membrane and the tetraphosphopeptide. Therefore, the tetraphosphorylated peptide species are efficiently eluted from the PAA membrane and can be satisfactorily detected under°acidic,°neutral,°and°alkaline°conditions°( Alumina is an amphoteric material whose surface electrical°properties°depend°on°solution°pH° [47]°and°the isoelectric point of the amorphous alumina is pH Ӎ 8 [48].°If°the°interactions°between°the°phosphopeptides and the PAA membrane are mainly by electrostatic interactions, the enrichment capacity would be influenced by solution pH. The isoelectric point of the PAA membrane made in phosphate acid is about 5.5 in Tris-HCl°buffer° [42].°Thus,°at°pH°Ͻ°5.5,°the°PAA membrane is protonated and has a positively charged surface.…”
Section: Selective Enrichment Of Phosphopeptides Using Paa Membrane Pmentioning
confidence: 99%
“…However, when we used o-phosphoric acid as the acid dopant in DHB as the matrix, the MS signal of tetraphosphopeptide (m/z 3122) and another phosphopeptide (m/z 2556) were observed°after°the°enrichment°process°with°PAA° (Figure°5).°In°addition°to°the°enhanced°ionization°of°phos-phopeptide, phosphoric acid might decrease the interactions between the PAA membrane and the tetraphosphopeptide. Therefore, the tetraphosphorylated peptide species are efficiently eluted from the PAA membrane and can be satisfactorily detected under°acidic,°neutral,°and°alkaline°conditions°( Alumina is an amphoteric material whose surface electrical°properties°depend°on°solution°pH° [47]°and°the isoelectric point of the amorphous alumina is pH Ӎ 8 [48].°If°the°interactions°between°the°phosphopeptides and the PAA membrane are mainly by electrostatic interactions, the enrichment capacity would be influenced by solution pH. The isoelectric point of the PAA membrane made in phosphate acid is about 5.5 in Tris-HCl°buffer° [42].°Thus,°at°pH°Ͻ°5.5,°the°PAA membrane is protonated and has a positively charged surface.…”
Section: Selective Enrichment Of Phosphopeptides Using Paa Membrane Pmentioning
confidence: 99%
“…1, [12][13][14] Martin and co-workers 1, 12 have studied the diffusivity inside nanopores by observing the mass transport across nanopore membranes. In their studies, they estimated the apparent diffusion coefficients of phenol derivatives in columnar alumina pores modified with octadecyltrimethoxysilane; the order of the estimated values was 10 -8 to 10 -6 cm 2 s -1 .…”
Section: Introductionmentioning
confidence: 99%
“…12 For the alumina membrane system, the diffusion coefficients of metal cations (10 -7 to 10 -6 cm 2 s -1 ) in unmodified alumina pores were reported and the surface effect on the diffusion behavior was discussed. 13 Fu et al 14 applied single-molecule fluorescence correlation spectroscopy to estimate an apparent diffusion coefficient of Nile Red in a surfactant-templated mesoporous silica thin film, and found that the diffusion coefficient was very small (∼10 -10 cm 2 s -1 ). These reported diffusion coefficients in nanopores are smaller than those in the bulk solution phase (∼10 -6 cm 2 s -1 ), and this slow diffusivity has sometimes been ascribed to the adsorption of molecules at the inner wall of a nanopore.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,8] Removing the alumina material by dissolution after filling the pores furnishes metal nanowires or tubes of oxidic materials. [6] Bluhm et al [9,10] have reported on the use of nanoporous alumina membranes for diffusion processes. A wide field of possible applications exist, such as novel drug delivery systems (operational without any mechanical or electrical building blocks).…”
Section: Introductionmentioning
confidence: 99%